Literatur Review: Faktor Risiko Attention Deficit Hyperactivity Disorder (ADHD) : Risk Factors of Attention Deficit Hyperactivity Disorder (ADHD): Literature Review - Adiputra, I Made Sudarma; Pinatih, G. N. Indraguna; Trisnadewi, Ni Wayan; Oktviani, Ni Putu Wiwik (Bali Medika Jurnal, 2021)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is a growth and development disorder in children characterized by impaired excessive activity and low attention of preschool-aged children. Children who suffer from ADHD will be very difficult to manage and tend to experience problems both at home or at school. This study literature aimed to obtain risk faktors for the incidence of ADHD. Methods and Results: The method used is literature review, search database using several sources from the database: EBSCO HOST, Proquest, PubMed, Scient Direct and Springer Link 2010-2020 publications, the keywords “Risk Faktors”,”adhd or attention deficit hyperactivity disorder” Boolean operator “AND”. There are total of 309 articles found in accordance with these keywords. The article was evaluated according to desirable criteria: full text, the language used and the suitability of the design, a total of 18 articles that are used for this review. Discussion: Risk faktors that increase the incidence of ADHD: Exposure to cigarette smoke, smoking and consuming alcohol during pregnancy, obese pregnant women, birth history with low birth weight (LBW) and premature birth, APGAR low score at birth, genetic and environmental conditions, socioeconomic parents, age of parents and birth history of sectio caesaria (SC).